2012
DOI: 10.1124/jpet.111.190918
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CCX140-B, an orally bioavailable antagonist of the CCR2 chemokine receptor, for the treatment of type 2 diabetes and associated complications

Abstract: The following manuscript was published as a Fast Forward article on February 29, 2012: Sullivan TJ, Dairaghi DJ, Krasinski A, Miao Z, Wang Y, Zhao BN, Baumgart T, Berahovich R, Ertl LS, Pennell A, Seitz L, Miao S, Ungashe S, Wei Z, Johnson D, Boring L, Tsou C-L, Charo IF, Bekker P, Schall TJ, and Jaen JC, Characterization of CCX140-B, an orally bioavailable antagonist of the CCR2 chemokine receptor, for the treatment of type 2 diabetes and associated complications. J Pharmacol Exp Ther jpet.111.190918; doi:10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…A number of small-molecule CCR2 antagonists have advanced to clinical trials in humans, with different degrees of success [73]. One of these, CCX140-B [74], decreased inflammation in preclinical models of sterile peritonitis and improved glucose tolerance in obese mice [75]. A Phase I clinical trial informed for the dose chosen for ongoing Phase II trials [75].…”
Section: Chemokine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of small-molecule CCR2 antagonists have advanced to clinical trials in humans, with different degrees of success [73]. One of these, CCX140-B [74], decreased inflammation in preclinical models of sterile peritonitis and improved glucose tolerance in obese mice [75]. A Phase I clinical trial informed for the dose chosen for ongoing Phase II trials [75].…”
Section: Chemokine Receptorsmentioning
confidence: 99%
“…One of these, CCX140-B [74], decreased inflammation in preclinical models of sterile peritonitis and improved glucose tolerance in obese mice [75]. A Phase I clinical trial informed for the dose chosen for ongoing Phase II trials [75].…”
Section: Chemokine Receptorsmentioning
confidence: 99%
“…It was also reported that insulin infusion can exert an anti-inflammatory effect by suppressing plasma concentrations of key chemokines involved in monocyte trafficking including CCL2 and CCL5 and their respective receptors CCR2 and CCR5 (107). Due to the importance of monocytes/macrophages in the pathology of diabetes, anti- mouse CCL2 drugs (108) and CCR2 antagonists (109) have been developed to treat T2DM diabetic nephropathy and other associated complications. The validation and applicability to T2DM patients is still uncertain.…”
Section: Chemokines In Health and Diseasementioning
confidence: 99%
“…Human trials are in progress studying a macrophage homing molecule antagonist with early promising results (50). Targeting specific pathogenic macrophage subpopulations is another important line of research.…”
Section: Immunotherapy For Metabolic Diseasementioning
confidence: 99%